FARID ESACK'S QUR’ANIC HERMENEUTICS OF PLURALISM FOR INTERRELIGIOUS COOPERATION IN INDONESIA - Muttaqin, Zaenal (Indonesian Journal of Islamic Literature and Muslim Society, 2020)
In contemporary Islamic thought, religious pluralism has been a discourse that many Moslem scholars have introduced to the Islamic community. One of the scholars is Dr. Farid Esack, a South African exegete who is also well-known as a human right activist. Brought up under an apartheid regime ruling South Africa, Esack is of a certain opinion that religion should function to struggle against any unjust order. To make a radical and fundamental change, according to Esack, there is no way but to constructively reinterpret religious discourse and role so as to be a tool of liberation. Using yet controversial a hermeneutical analysis on the Qur'an, Farid Esack raises the idea of pluralism dealing critically with the struggle against oppression and toward liberation for South Africa.